356. The Role of Procalcitonin in Antimicrobial Stewardship Among Cancer Patients Admitted with COVID-19. (4th December 2021) - Dagher, Hiba; Chaftari, Anne-Marie; Hachem, Ray Y; Jiang, Ying; Malek, Alexandre; Garnes, Natalie J Dailey; Borjan, Jovan; Mulanovich, Victor; Raad, Issam I
Abstract: Background: Procalcitonin (PCT) has been used to guide antimicrobial therapy in bacterial infections. With the wide spread use of empiric use of antibiotics in cancer patients admitted with COVID-19 disease, we aimed to evaluate the role of PCT in decreasing the duration of empiric antimicrobial therapy among cancer patients admitted with COVID-19. Methods: We conducted a retrospective study of cancer patients admitted to MD Anderson Cancer Center who had a PCT test done within 72 hours of admission following their COVID-19 diagnosis between March 1, 2020 and June 6, 2021. Patients were divided into 2 groups of PCT < 0.25 ng/mL and PCT >=0.25 ng/mL. We assessed pertinent cultures including blood and respiratory, as well as antibacterial use and duration of empiric antibacterial therapy. Results: We identified 544 patients with a median age of 62 years (range, 14-93). There were 312 (57%) patients that had at least one culture obtained from a sterile or infected site within 7 days following admission. None of the patients who had PCT< 0.25 had a positive culture whereas 41/111 (37%) patients with PCT >= 0.25 had at least one positive culture [P< 0.0001]. Among the 373 patients who had a PCT < 0.25, 129 (35%) patients received more than 72 hours of IV antibiotics compared to 87/171 (51%) among patients with PCT >=0.25 [P= 0.0003]. Conclusion: These results confirm the correlation between a PCT level greater than 0.25 and a documented bacterial infection. Furthermore, procalcitonin could be useful in enhancing antimicrobial stewardship in cancer patients with COVID-19 by reducing the duration of antimicrobial therapy beyond the initial empiric 72 hours until PCT results become available. Disclosures: Natalie J Dailey Garnes, MD, MPH, AlloVir (Other Financial or Material Support, collaborator on research protocol)